Estudo da ação do intemperismo natural e artificial nos componentes químicos do lenho de três espécies madeireiras da Amazônia por espectroscopia de infravermelho próximo (FT-NIR) - (:unkn) unknown (Universidade Federal do Amazonas, 2014)
Wood when exposed to sunlight undergoes chemical degradation surface which causes a change of color and weakening its mechanical strength. This process of surface degradation is commonly called weathering process. Although providing satisfactory results, the conventional methods of analysis expose the operator to hazardous environments and / or toxic materials necessary in the analyzes. An alternative to traditional destructive evaluation would be to use non-destructive methods for evaluating properties of wood. As an option to perform the analysis nondestructively technology emerges near infrared Fourier transform (FT-NIR), which gives information about the chemical properties of a sample. The study aimed to evaluate the effects of weathering on the main macroconstituintes wood (cellulose and lignin) through FR-NIR technology. To achieve the proposed objective we chose to use timber waste from three Amazonian forest species: Maçaranduba (Manilkara huberi), Tauari (Couratari stellata) and Marupá (Simarouba amara) chosen for having high, medium and low density respectively and relative insertion timber market in the Amazon region. The samples were subjected to methods of natural and artificial weathering, where the natural weathering test lasted a year and the artificial weathering test lasted 27 weeks. The samples were analyzed weekly with the FT-NIR spectrophotometer over the period of natural and artificial weathering tests. The test results showed changes in spectra during the processes of natural and artificial weathering and UV light prove that the chemical structure of modified wood by decomposition of the chemical constituents and the formation of lignin-related cellulose compounds. In the natural and artificial weathering test maçaranduba takes longer to break down cellulose and lignin, but with the increase in period of weathering, the peaks related to pulp and lignin change and decrease and tend. The rate of decomposition of the wood surface is characteristic of each species.
Keywords: Intemperização natural e artificial; FT-NIR; Madeira - Degradação química; Madeira - Celulose e lignina; Natural and artificial weathering; Cellulose and lignin; CIÊNCIAS AGRÁRIAS: RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL